Application of Inner Speech in the Motor Learning Context: A Validation Study - Dana, Amir; Brinthaupt, Thomas M. (Health Nexus, 2025)
This study addresses the absence of suitable tools for evaluating the frequency and content of inner speech during the acquisition of new motor skills by adapting the Learning-Specific Inner Speech Scale (Xiang et al., 2020) for a motor learning context. We assessed the modified scale, termed the Motor Learning-Specific Inner Speech Scale (MLISS), focusing on its factor structure, internal consistency, and content validity among young adults in Study 1. A total of 325 university students (145 females) participated, completing the MLISS, which comprises 16 items across four dimensions of inner speech: self-criticism, self-reinforcement, self-management, and social assessment. In Study 2, 149 university students (58 females) completed the MLISS and executed three basketball skills: shooting, passing, and dribbling. Data analysis employed confirmatory factor analyses and structural equation modeling, which confirmed the proposed scale structure. Notably, the self-reinforcement and self-management dimensions of the MLISS showed significant correlations with basketball performance, affirming the measure’s construct validity. These findings indicate that the MLISS is a valid tool for assessing inner speech frequency in motor learning, marking the first extension of an existing inner speech measure into this domain.